Proceedings from the Ice Hockey Summit III: Action on Concussion - Aynsley M Smith; Patrick A Alford; Mark Aubry; Brian Benson; Amanda Black; Alison Brooks; Charles Burke; Ryan D'Arcy; David Dodick; Michael Eaves; Chad Eickhoff; Kristen Erredge; et al. (Sapientia Publishing Group, 2019)
Objectives The Ice Hockey Summit III provided updated scientific evidence on concussions in hockey to inform these five objectives: (1) describe sport related concussion (SRC) epidemiology, (2) classify prevention strategies, (3) define objective, diagnostic tests, (4) identify treatment and (5) integrate science and clinical care into prioritized action plans and policy. Methods Our action plan evolved from 40 scientific presentations. The 155 attendees (physicians, athletic trainers, physical therapists, nurses, neuropsychologists, scientists, engineers, coaches and officials) voted to prioritize these action items in the final Summit session. Results (1) establish a national and international hockey data base for SRCs at all levels; (2) eliminate body checking in Bantam youth hockey games; (3) expand a behavior modification program (Fair Play) to all youth hockey levels; (4) enforce game ejection penalties for fighting in Junior A and professional hockey leagues; (5) establish objective tests to diagnose concussion at point of care (POC); and (6) mandate baseline testing to improve concussion diagnosis for all age groups. Conclusions Expedient implementation of the Summit III prioritized action items is necessary to reduce the risk, severity and consequences of concussion in the sport of ice hockey.